Cardiotoxicity of doxorubicin – causes, prevention, prospects - Wesołowski, Paweł; Budzeń, Kamil; Bąk, Sebastian; Sygacz, Oliwer; Stachura, Tomasz (Journal of Education, Health and Sport, 2022)
Introduction: Doxorubicin is one of the most reliable anthracycline chemotherapeutics. Its high efficacy in treating a large range of cancers, however, comes hand in hand with complications. A hallmark of anthracycline drugs, and also their most common side effect, is heart failure caused by the development of dilated cardiomyopathy. Purpose of the study: The purpose of our work is to present the current state of knowledge about the causes of doxorubicin cardiotoxicity and to present known ways to minimize the negative impact on the patient’s health. Materials and Methods: We performed a non-systematic review of the Polish and English-language literature available in the database, using the keywords: , doxorubicin"; , anthracyclines"; , cardiotoxicity"; , cardiomyopathy"; , chemotherapy". Results: Doxorubicin is counted among the first-generation anthracycline cytostatics widely used in cancer chemotherapy. The enormous potential of anthracyclines is a motivator for further attempts to improve these molecules and eliminate side effects. The methods developed so far have led to a reduction in the frequency of cardiovascular incidents, but the risks associated with the use of these drugs are still relatively high and the cost of liposomal forms is high. Summary: The current state of knowledge identifies promising options for improving the well-being of patients undergoing treatment with chemotherapeutic agents. Hopes for effective analogs free of cardiotoxic effects are reasonable, and the use of companion substances is an additional possibility.